2012
DOI: 10.1093/mnras/sts381
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the H2 emission and the physical structure of planetary nebulae

Abstract: Mid-IR observations of planetary nebulae (PNe) have revealed diffuse emission associated to their main nebular shells and outer envelopes or haloes. The interpretation of this emission is uncertain because the broad-band mid-IR images may include contributions of different components. In particular, the Spitzer IRAC 8 µm images, that best reveal these nebular features, can include contributions not only of H 2 lines, but also those of ionic species, PAH features, and thermal dust continuum emission. To investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 58 publications
2
35
1
Order By: Relevance
“…As more sensitive observations are been carried out, many exceptions to this rule have been reported. Large, very evolved PNe of different morphological groups have been found to display emission in H2 lines (Marquez-Lugo et al 2013). There is not a tight correlation between occurrence of H2 emission and bipolar morphology in fluorescence-excited sources (García-Hernández et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As more sensitive observations are been carried out, many exceptions to this rule have been reported. Large, very evolved PNe of different morphological groups have been found to display emission in H2 lines (Marquez-Lugo et al 2013). There is not a tight correlation between occurrence of H2 emission and bipolar morphology in fluorescence-excited sources (García-Hernández et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These observations show that H2 emission is predominantly detected in the equatorial regions of bipolar PNe (hereafter BPNe), as self-and dust-shielding of UV photons at PDRs in their dense equatorial regions can provide a safe haven for molecules. Although BPNe are E-mail: amarquez@iaa.es the brightest H2-emitters, the presence of molecular hydrogen is not exclusive to BPNe; sensitive observations have proven that H2 emission can also be detected in PNe with ellipsoidal or barrel-like morphologies (Marquez-Lugo et al 2013). The high-spatial resolution of these observations unveil that the H2 emission from the equatorial ring of BPNe arises from knots and clumps embedded within the ionized material of the ring rather than from a PDR (Manchado et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…This H 2 emission line has been detected in a number of Galactic PNe (e.g., Kastner et al 1994Kastner et al , 1996Latter et al 1995;Schild 1995;Shupe et al 1995;Guerrero et al 2000;Arias et al 2001;Ramos-Larios et al 2008Marquez-Lugo et al 2013 as well as proto-PNe (e.g., Hrivnak et al 2008;Forde & Gledhill 2012). Imaging studies of the H 2 images of PNe have revealed that the H 2 2.122 μm emission in PNe is generally associated with a bipolar morphology (e.g., Webster et al 1988;Zuckerman & Gatley 1988); this is known as Gatley's rule, and the possible astrophysics for this association is still discussed today (e.g.,…”
Section: Introductionmentioning
confidence: 86%
“…The association between H 2 emission and the bipolar morphology of PNe was discussed by Kastner et al (1994Kastner et al ( , 1996, who defined the so-called Gatley's rule, which was later confirmed by a number of imaging surveys (e.g., Hora & Latter 1996;Hora et al 1999;Guerrero et al 2000;Marquez-Lugo et al 2013). It also has been suggested that bipolar PNe evolved from the more massive low-and intermediate-mass stars (1.5-2.0 M ☉ ; e.g., Peimbert & Torres-Peimbert 1983;Corradi & Schwarz 1995).…”
Section: H 2 Emission and Bipolaritymentioning
confidence: 91%
“…The number of PNe harboring H 2 has recently been considerably increased by the UWISH2 survey (Froebrich et al 2015, Gledhill, this volume), in which 284 extended H 2 sources are identified as PNe or PN candidates. H 2 emission appears stronger in bipolar PNe with equatorial rings (Marquez-Lugo et al 2013, and reference therein). Manchado et al (2015 and this volume) presented high-resolution H 2 images showing that the H 2 emission in the central torus appears clumpy rather than uniform, and suggested that those clumps might eventually populate the ISM and contribute to the baryonic dark matter.…”
Section: Small Gas-phase Moleculesmentioning
confidence: 78%